Age estimation of unaccompanied minors: A portuguese overview - Pereira, Cristiana Palmela (2015)
"In the past decade there has been a considerable increase in the number of unaccompanied asylum seeking children, many of whom appeared to be older than their given age. Dental age assessment has been included as part of the asylum seeking process in Portugal since the Law n. º 27/2008 dated 30 June (the “Asylum Law”). The legal framework of the forensic examination is based in biomedical ethics. The aim is to find the frequency of unaccompanied asylum seeking children with dental evidence of being older 18 years during the period between 2009 and 2013. In this period age estimations have been performed on 82 unaccompanied asylum seeking children whose given ages were queried by the Aliens and Bored Service – SEF, to the South Branch of National Institute of Legal Medicine and Forensic Sciences from Portugal. The dental development was studied on ortopantomograpic radiographs and the developing teeth staged from the tables according to Liversidge (2008), Mincer et al. (1993), Kullmanet al. (1992) and Haavikko (1970). If the dental development was complete, the dental age was estimated from Kvaal et al. (1995). The majority of the unaccompanied asylum seeking children clamed to came from Guinea Conakry, Nigeria, Guinea Bissau, Syria, Congo, Morocco and other African countries and non-African countries. There was no statistical significant difference between sexes. The majority gave the age as being 14 or 15 years (70%). Forty percent were found to be 18 years or older by the dental methods. Fifty percent were in need of dental treatment."